Analisis Manajemen Risiko dan Analisis SWOT pada UMKM Ushwoohe dalam Industri Sepatu Thrifting - Amira Muthi Ghassani; Alma Aulia Siffa; Susi Nurohimah; Tini Kartini; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study analyzes risk management in Uswhoose, a micro enterprise selling thrifted footwear, using a qualitative descriptive approach through interviews and supporting data. The findings reveal four main risk categories: market, operational, human resource, and financial risks, driven by trend changes, inconsistent product quality, limited employee skills, and unstable cash flow. SWOT analysis shows strengths such as competitive pricing and flexible sales channels, while weaknesses include product inconsistency and limited HR capacity. Opportunities arise from the growing thrift market and digital platforms, whereas threats include intense competition. Risk mitigation is strengthened through SOP implementation, employee training, and improved financial control.